Enhancing toughness of polypropylene and polystyrene –application of styrene-b-ethylene-alt-butylenes-b-styrene - Ezuan Mustafa, Mohd. Shahril (Faculty of Chemical and Natural Resource Engineering, 2007)
Since toughness is an important mechanical property, impact modifiers are widely used to enhance the impact properties of many thermoplastics. This paper focused on the effectiveness of styrene-b-ethylenealt- butylenes-b-styrene (SEBS) as an impact modifier in polypropylene (PP) and polystyrene (PS). In this study, blends of PP/SEBS and PS/SEBS were prepared using single screw extruder. The concentration of SEBS varied from 5 to 20phr of polymer for both PP and PS. After mixing and pelletizing, the dried pellets were injection molded and tested for mechanical properties. With increasing SEBS content, the increase in impact properties is more significant in PP/SEBS blends compared to PS/SEBS blends. Tensile test showed a slightly decrease of tensile strength for both blends. For PP/SEBS blends of 15phr SEBS content and above, no sample break was observed during the tensile test. A decrease in flexural modulus of both blends with increasing SEBS contents was observed, with a more siginificant decrease in PS/SEBS blends. Overall, SEBS is shown to be more effective as an impact modifier in PP compared to PS